Real-Time Monitoring for Smart Logistics - Mokhtar, Muhammad Adham; Ubin, Aizan (Evolution in Electrical and Electronic Engineering, 2022)
Unexpected occurrences like as temperature swings and humidity changes have the potential to devalue the value of products being carried. Unwanted occurrences must be avoided, and flaws in the delivery process must be addressed. The Internet of Things (IoT) allows us to determine when, where, and how certain abnormalities in the supply process happened. Because IoT can be integrated into traditional supply chains to track, trace, and monitor vehicle movement, it may be able to solve some transportation issues. This project is now presenting the design and implementation of real-time data monitoring for smart logistics. The goal of this project is to sense temperature, humidity, and GPS data and send the data via the Favoriot Platform. Furthermore, this system allows these data to be sent to the transportation firm as a notification for an alert system. The scope of the research is to sense the range of temperature (-20°C - 10°C) and level of humidity (60% - 100%), and current location in transportation. The methodology was developed using selected hardware and software such as DHT22, GPS module, Hibiscus Sense ESP32, Arduino IDE, Wi-Fi connectivity and Favoriot Platform. Based on the result, the real-time data have been successfully recorded and compared with the simulated data to make sure that the results designed for this project are correct and in accordance with the theory.